19F and 1H magnetic resonance strategies for metabolic studies on fluorinated xenobiotics: Application to flurbiprofen [2-(2-fluoro-4-biphenylyl)propionic acid] - Wade,KE; Wilson,ID; Troke,JA; Nicholson,JK (Journal of Pharmaceutical and Biomedical Analysis, 1990)
Strategies for the use of 1H and 19F nuclear magnetic resonance (NMR) spectroscopy as an aid to the study of the metabolic fate of fluorinated drugs are discussed with reference to the application of these methods to flurbiprofen metabolism in man. 1H and 19F NMR analysis of untreated urine enabled the detection of two major and eight minor metabolites of the drug. The two major metabolites were identified using a combination of NMR spectroscopy, solid-phase extraction chromatography with 19F and 1H NMR detection and chemical hydrolysis to a flurbiprofen glucuronide and the glucuronide of the 4-hydroxy metabolite. 1H-19F 2D shift correlated spectroscopy and spin-echo difference experiments are discussed in relation to their use in the structural identification of drug metabolites. © 1990.